Combined Effects of pH Adjustment and Bentonite Addition Timing on Protein Stability of Sauvignon Blanc Wine - Wenfeng Hung; Roland Harrison; James Morton; Mike Trought; Andy Frost; Bin Tian (Australian Journal of Grape and Wine Research)
Background and Aims. Bentonite fining is commonly used in white wine production, which can lead to the loss of wine volume and aroma compounds. Many factors influence the efficacy of bentonite fining. The effect of pH adjustment and timing of bentonite addition were studied for their combined effects on Sauvignon Blanc wine protein haze formation and bentonite requirement at microscale and commercial scale. Methods and Results. Three bentonite addition timings were conducted on a juice pH adjustment trial: before fermentation, during fermentation, and after fermentation. The hot and cold test was utilized to determine the bentonite requirement for protein stabilization. Wine proteins were analyzed using a modified Coomassie brilliant blue (CBB) assay, lithium dodecyl sulphate polyacrylamide gel electrophoresis (LDS-PAGE), and sodium dodecyl sulphate capillary gel electrophoresis (SDS-CGE). Lower juice pH (2.80 and 3.00) resulted in sluggish fermentation, whereas the presence or absence of bentonite during fermentation showed similar fermentation kinetics at each pH. The presence of bentonite remaining in contact with ferment improved the completion of fermentation for the most sluggish ferment (pH 2.80). Commercial wine made from same batch of juice was adjusted to different pH values, and low-pH wines had a lower wine protein content and an increasing protein adsorption efficiency of bentonite fining, leading to lower bentonite requirement. Conclusions. Bentonite addition during fermentation was the most efficient in protein removal but fining after fermentation required the least overall bentonite dosage. The different fermentation scales (i.e., microscale versus commercial scale) slightly affected wine protein contents but not molecular weight (MW) profiles. Protein contents and MW profiles in stabilized wines were affected by the original juice pH with more complex patterns from high-pH juice. Significance of the Study. The findings of this study provide valuable information on optimization of bentonite fining to minimize the dosage so as to reduce the loss of wine volume and quality.